A Fault Area Location Method in Distribution Network With DG - Zhongjian Kang; Aina Tian; Zhe Bai (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
To precisely locate the grounded fault area in distribution network with DG, a new grounded fault area location algorithm based on three-phase impedance model and fault features in distribution network with DG is proposed in this paper. This method establishes three-phase impedance model if the distribution network with DG, analyzes and extracts the fault characteristics on the basis of the three phase impedance model of distribution network with DG. According to the characteristic of the feature value in the fault point, this method traverses all the nodes and gets the fault associated nodes. The method proposed in this paper was tested in a sixty nodal distribution system with six DGs, the result of the method verifies that the method can precisely locate the grounded fault area in distribution network with DG. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3548